Study on Sensitivity Differences of Critical Spontaneous Ignition Temperature between Alcohol and Hydrocarbon Fuels Based on Reaction Pathway - Qiang Liu; Zhongchang Liu; Xiaoming Ren; Yongqiang Han; Jun Wang; Jian Fang (Energies, 2019)
In this article, the critical spontaneous ignition temperature of both hydrocarbon and alcohol fuel was acquired on a constant volume combustion bomb platform by slowly heating the inner charges, and then followed by using the CHEMKIN-PRO software to simulate the auto-ignition-dominated characteristic and parameter sensitivity of the two kinds of fuels. Results revealed that in different conditions, the critical spontaneous ignition temperature of methanol changed dramatically, with a maximum temperature of 50 K, while the counterpart temperature of n-heptane remained an invariable value of 553 K within a large changeable scope of temperature, and only a maximum temperature of 10 K was observed. The maximum difference of spontaneous ignition temperature between methanol and n-heptane reached 270 K. At the same time, a minimum difference of 170 K was obtained as well. The complete reaction of methanol requires 5 steps, involving 6 components and 11 elementary reactions. However, for the comparative part-n-heptane, more than 20 main self-ignition reactions were involved, which indicated that the whole reaction process of n-heptane has more reaction pathway branches and it was much more complicated compared to methanol. The differences of the reaction pathways triggered a considerable distinction of critical self-ignition temperature between the two charges, making a “step-by-step„ spontaneous ignition combustion mode possible. In this way, a further high-efficient and clean combustion can be available to cater to much more stringent emission regulations in the future.